L'industrie mondialisée du travail domestique aux Philippines Recruter, former et exporter l'altérité - Debonneville, Julien (De l'Orient à l'Occident, 2023)
Because of their many supposed qualities, women from the countries of the Global South have become a coveted workforce when it comes to taking care of people and households. Among them, women from the Philippines have become particularly praised for their "dedication to work", "patience" and "docility". This book analyses how, in the Philippine migration industry, these domestic workers are recruited and trained before being deployed to Asia, the Middle East, Europe and North America. Based on an ethnographic study carried out within Philippine migration institutions located in Manila, this book examines how the institutional making of this globalised domesticity is closely linked to processes of othering which contribute to disciplining, moralising and normalising these women. This research examines how, through the practices of recruiting, training and deploying these women, "Filipina" otherness is co-constructed by multiple local, national and transnational actors, such as recruitment agencies and pre-migration training centres. This book thus offers the opportunity to consider the construction of otherness from the perspective of the migration industry and the colonial history of the archipelago. It contributes to the reflections on the coloniality of power, the gendered and racial construction of qualification, the normalisation of bodies and the transnational governance of migration.